A new Nucras Gray, 1838 (Squamata: Lacertidae) from the Strandveld of the Western Cape, South Africa - Bauer, Aaron M.; Childers, Jackie L.; Broeckhoven, Chris; Mouton, P. Lefras N. (Zootaxa, 2019)
A striking new sandveld lizard of the Nucras tessellata group is described from the Lambert’s Bay Strandveld of the Western Cape Province, South Africa. It is sister to the clade N. livida + N. tessellata, and is phenetically most similar to N. tessellata, from which it differs in its more elongate body and possibly increased number of presacral vertebrae and patternless orange dorsal coloration. The form elegans, described as a species by Andrew Smith (1838), but treated as an infrasubspecific variant by Broadley (1972), also exhibits weak patterning, but is likely a regional color variant. Nucras aurantiaca sp. nov. is the ninth member of the genus found in southern Africa. Its discovery in the well-collected coastal Western Cape suggests that further herpetofaunal surveys are needed in this region, which is threatened by agricultural activity and tourism-related development.